Fertilizer management of potato (Solanum tuberosum) variety Kufri Frysona for higher yield, good fry quality, profitability and storability - Kumar, Parveen; Kumar, Rajeev; Kumar, Dinesh; Singh, Sukhwinder; Sandhu, K.S.; Singh, B.P. (Annals of Agricultural Research, 2016)
The field experiment was conducted at Modipuram (India) in split-plot design having three potato varieties in main plot and four fertilizer management treatments in sub-plot with three replications. Fertilizer management treatments did not influence the growth parameters as well as graded tuber number except French fry grade (FFG), which was maximum at 270 N+80 P2O5+150 K2O kg/ha. French fry grade tuber numbers were statistically similar between Kufri Surya and Kufri Frysona but lower in Kufri Chipsona-1. Over varieties, different fertilizer management treatments did not show any significant change in tuber yield recorded under different size categories. Among varieties, FFG tuber yield were at par between Kufri Frysona (13.7 t/ha) and Kufri Surya (15.6 t/ha) but significantly higher than Kufri Chipsona-1 (8.8 t/ha). Across potato varieties, tuber specific gravity was recorded significantly higher in treatment F1 (1.083) than F3 (1.081) and F4 (1.081), where N and K rates was higher by 25%; other processing quality traits viz. tuber dry matter content, French fry colour and glucose content did not vary significantly due to different fertilizer management treatments. Kufri Frysona recorded maximum tuber specific gravity (1.087) and dry matter content (23.8%) which was significantly higher than Kufri Chipsona-1 and Kufri Surya. During long-term storage, the fry colour was in acceptable range in F1 and F3 treatment for Kufri Frysona at all dates of storage (upto 165 days). The glucose levels were less than 35 mg/100 g fresh weight in all the fertilizer management treatments and after all the dates of storage for Kufri Frysona. Across varieties, net income and benefit cost ratio were statistically higher under fertility regime F1 (270 N+ 80 P2O5+ 150 K2O kg/ha, where all NPK was applied through soil application). Among varieties, Kufri Frysona had highest net returns as well as B:C followed by Kufri Chipsona-1 and lowest in Kufri Surya. To realize higher French fry grade tuber yield, maximum profits and acceptable fry quality at harvest and during long-term storage the newly developed French fry variety Kufri Frysona may be grown with fertilizer dose of 270 N [N135 (planting) + N135 (earthing)] + 80 P2O5 + 150 K2O kg/ha as soil application